2014
DOI: 10.1086/678270
|View full text |Cite
|
Sign up to set email alerts
|

Class Advantage and the Gender Divide: Flexibility on the Job and at Home

Abstract: Using a survey, interviews, and observations, the authors examine inequality in temporal flexibility at home and at work. They focus on four occupations to show that class advantage is deployed in the service of gendered notions of temporal flexibility while class disadvantage makes it difficult to obtain such flexibility. The class advantage of female nurses and male doctors enables them to obtain flexibility in their work hours; they use that flexibility in gendered ways: nurses to prioritize family and phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 51 publications
2
98
0
2
Order By: Relevance
“…Research based on nationally representative data indicates that black men, on average, report more egalitarian ideologies (Cotter, Hermsen, and Vanneman 2011;Kane 2000) and perform more femininetyped work such as childcare and housework compared to white men in intimate partnerships (Vespa 2009). This suggests that black men may hold a greater willingness to participate in feminine-typed work; although, this might instead result from fewer economic resources to outsource childcare and housekeeping tasks (Gerstel and Clawson 2014). Hispanic men, in contrast, typically express more traditional gender ideologies than white men and report performing fewer household responsibilities than white men (Vespa 2009;Cotter et al 2011), which suggests that Hispanic men would be less inclined to seek out female-dominated jobs.…”
Section: Discussionmentioning
confidence: 99%
“…Research based on nationally representative data indicates that black men, on average, report more egalitarian ideologies (Cotter, Hermsen, and Vanneman 2011;Kane 2000) and perform more femininetyped work such as childcare and housework compared to white men in intimate partnerships (Vespa 2009). This suggests that black men may hold a greater willingness to participate in feminine-typed work; although, this might instead result from fewer economic resources to outsource childcare and housekeeping tasks (Gerstel and Clawson 2014). Hispanic men, in contrast, typically express more traditional gender ideologies than white men and report performing fewer household responsibilities than white men (Vespa 2009;Cotter et al 2011), which suggests that Hispanic men would be less inclined to seek out female-dominated jobs.…”
Section: Discussionmentioning
confidence: 99%
“…Achieving these new standards takes resources. For example, successfully negotiating household tasks might benefit from flexible jobs (Gerstel and Clawson 2014). Moreover, finding a compatible partner likely benefits from wide, supportive social networks, something associated with higher levels of education and majority white racial status (Kao and Joyner 2004;McPherson, Smith-Lovin and Brashears 2006).…”
Section: The Diverging-destinies Perspectivementioning
confidence: 99%
“…Two other studies found distinct class differences in fathering styles (Gerstel and Clawson 2014;Shows and Gerstel 2009). Both studies interviewed physicians and emergency medical technicians (EMTs) to show that employment conditions were largely responsible for class differences in fathering.…”
Section: Qualitative Evidencementioning
confidence: 90%
“…These trends encourage men's engagement in care work, in that two of the strongest predictors of fathers providing childcare are later age at first birth and dependence on wives' pay (for a review of household labor research, see Coltrane 2006;Gerstel and Gallagher 2001;Raley, Bianchi, and Wang 2012). Another factor encouraging men's engagement in care work is the dispersion of work schedules; that is, men who work nights while their partners work days are more likely to do housework and provide childcare (Gerstel and Clawson 2014;Presser 2003;Shows and Gerstel 2009). My argument, then, is that economic changes associated with the emergence of a new economy have created the structural conditions that encourage men (especially those in the working class) to take part in family care work.…”
Section: The New Economy and Men's Paid Workmentioning
confidence: 99%
See 1 more Smart Citation